Stable isotopic variation in tropical forest plants for applications in primatology. Issue 10 (7th October 2015) - Blumenthal, Scott A.; Rothman, Jessica M.; Chritz, Kendra L.; Cerling, Thure E.
Abstract : Stable isotope analysis is a promising tool for investigating primate ecology although nuanced ecological applications remain challenging, in part due to the complex nature of isotopic variability in plant‐animal systems. The aim of this study is to investigate sources of carbon and nitrogen isotopic variation at the base of primate food webs that reflect aspects of primate ecology. The majority of primates inhabit tropical forest ecosystems, which are dominated by C3 vegetation. We used stable isotope ratios in plants from Kibale National Park, Uganda, a well‐studied closed‐canopy tropical forest, to investigate sources of isotopic variation among C3 plants related to canopy stratification, leaf age, and plant part. Unpredictably, our results demonstrate that vertical stratification within the canopy does not explain carbon or nitrogen isotopic variation in leaves. Leaf age can be a significant source of isotopic variation, although the direction and magnitude of this difference is not consistent across tree species. Some plant parts are clearly differentiated in carbon and nitrogen isotopic composition, particularly leaves compared to non‐photosynthetic parts such as reproductive parts and woody stem parts. Overall, variation in the isotopic composition of floral communities, plant species, and plant parts demonstrates that stable isotope studies must include analysis of local plant species and parts consumed by the primates under study from within the study area. Am. J. Primatol. 78:1041–1054, 2016. © 2015 Wiley Periodicals, Inc.